Cleveland Browns - Abdo, Kenny, 1986- (2022)
This title focuses on the Cleveland Browns and gives information related to the team's origin in the NFL, their journey through the decades, and highlighting their Hall of Fame players.
Includes index.
Ages 7-12
Keywords: Cleveland Browns (Football team : 1946-1995) -- Juvenile literature; Cleveland Browns (Football team : 1999- ) -- History -- Juvenile literature; Football -- Juvenile literature; High interest-low vocabulary books